Upaya Meningkatkan Proses Pembelajaran Melalui Supervisi Kelas di SMP Negeri 13 Langsa Tahun Pelajaran 2022/2023 - husniati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research was conducted with the aim of knowing whether class supervision at SMP Negeri 13 Langsa can improve the learning process. The results of school action research can be concluded as follows, in cycle 1 activities the results obtained from the number of supervised teachers 16 people obtained the results of 6 people who have an average value of 60% which can already be categorized as good or equal to (37.5%) while 10 other people who have an average value of 50% are included in the sufficient category or equal to (62.5%). In cycle 2 activities, the results obtained were that the number of teachers was 16 people who were supervised. Again, there were 12 people who had an average score of 60% which could be categorized as good or equal to (75%), while 4 more people had an average score of 50% included in enough category or equal to (25%). To improve the learning process in schools, the principal should make an intensive class visit supervision program every semester, so that all teachers carry out learning activities properly.